Feasible Study on Dental Restoration Using Time Compression Technologies / Nurul Hatiqah Harun...[et al.] - Harun, Nurul Hatiqah; Kasim, Mohd Shahir; Raja Abdullah, Raja Izamshah; Boejang, Hambali; Attan, Hassan (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Time compression technologies (TCT) are concurrent engineering approaches employed during product and process development. TCT such as reverse engineering (RE) and rapid prototyping (RP) techniques are widely used in dentistry and medical sectors. Taking advantage of new technologies in computer-aided design (CAD) data, rapid mechanical prototyping makes it possible to fabricate complex shaped three-dimensional (3D) parts quickly using an RP machine. The current practice of dental restoration in dental laboratories is time consuming. Therefore, this paper presents the possibility of a TCT approach that can be applied to replace this conventional process in producing dental crowns. The TCT approach has been applied and compared to the conventional approach throughout this experiment. The TCT process is faster and simpler than the conventional process. The results show that the crowning process is difficult to be fabricated correctly. Problems arise due to the limitations of the Projet 3500 HD machine, which cannot build parts with a thickness of 300 μm or less.